The Implementation of Inductive Model in the Learning of Finding Religious Values in Short Stories "Robohnya Surau Kami" by A.A. Navis - Nendah Siti Nurfuadah (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2018)
This article reveals the effectiveness of using inductive learning models to find religious values in the short story. The method used in the study is PTK. The experiment was conducted in three cycles, each cycle consists of two meetings. The study was conducted in grade XI MAN Cianjur. The results showed that inductive models can enhance the learning process, especially the attention of students in learning and students cooperation in group discussions. In the first cycle, in terms of students attention, from 44 students there are 29 students (65.90%) paid attention, and in terms of cooperation of the students in group discussions, there were 27 students (61.36%) are cooperative. In the second cycle, from 44 students there were 33 students (75%) who paid attention, and regarding the cooperation of the group, there are 30 students (68.18%) who are cooperative. In the third cycle, from 44 students there are 38 students (86.36%) who paid attention, and regarding group cooperation there are 39 students (88.64%)who are cooperative. The student’ results in the first cycle obtained an average value of 68.64, in the second cycle the average value was 77.16, and in the third cycle the average value was 91.82. Therefore, it is concluded that the implementation of inductive learning model on learning of finding religious values on the short story in class XI MAN Cianjur can enhance the learning process and student learning outcomes.Keywords: religious value, inductive models, processes and outcomes